Pressure and Deformation Measurement with Piezoresistive Sensors - Pimentel, José Henrique Fernandes (2020)
This dissertation shows us the processes to develop a sensor capable of measuring deformations of surfaces. The work englobes the processes of production and assemblage of the transducers, the electronics boards to read the signals from the transducers and, finally, the development of algorithms used to transform the signal of the sensor in readable information either for humans and other computers. The work starts with the study of the production and assemblage methods of the transducers. In this part, we used the screen printing technique to print the different layers of the transducer. After obtaining the printed transducer, we tested it, measuring only the main characteristics, as the variation of resistance with pressure. This gave us important information to proceed with the dimensioning of the measurement chain. The second part of this project, was focused in the design of the measurement chain. For this work, we projected a device that can adapt automatically to different values of sensors’ resistance. Because the transducers tested in this project have a hysteretic behavior, a mathematical model used to model the magnetic hysteresis was adapted to be used with piezoresistive sensors. This work meets the initial goal which was building a complete data acquisition system for a printed piezoresistive sensor. The proposed mathematical algorithm to model the resistance of piezoresistive sensors opens doors for future projects.